Software Engineering Techniques Third IFIP TC 2 Central and East European Conference, CEE-SET 2008, Brno, Czech Republic, October 13-15, 2008, Revised Selected Papers - Huzar, Zbigniew; Koci, Radek; Meyer, Bertrand; Walter, Bartosz; Zendulka, Jaroslav (Springer eBooks., 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the Second IFIP TC 2 Central and East-European Conference on Software Engineering Techniques, CEE-SET 2008, held in Brno, Czech Republic, in October 2008. The 20 revised full papers presented together with a keynote speech were carefully reviewed and selected from 69 initial submissions. The papers are organized in topical sections on requirements specification, design, modeling, software product lines, code generation, project management, and quality.